A CUT ON VIOLENCE AND HUMAN RIGHTS IN THE CONTEXT OF STREET COMMERCIAL SEX WORKERS OF A CITY IN THE METROPOLITAN REGION OF PORTO ALEGRE, RS. (Fiep Bulletin - online, 2013)
According to the Brazilian Constitution, all people are equal before the law, assuring inviolability of the right to life, freedom, equality, safety and property. This study was aimed to represent the violence and the human rights in the context of street commercial sex workers (CSW) of a city in the metropolitan region of Porto Alegre; in the prospect of aggression, conflicts with the police and detention. The methodology was characterized as quantitative, cross design, with consecutive sampling. For the data collection it was used a structured interview, with mostly closed questions. After informed consent, the interviewers started to collect data on the streets of the sampled city, as foreseen in the project approved by the Ethics Committee. A total of 22 female CSW, aged from 18 to 38 years were interviewed. With regard to aggression, the results indicated that 54.5% (12) of the CSW reported having been victim of aggression. Of these, 50% (6) were assaulted by customers, 25% (3) by their current or former stable partner, 16.7% (2) by customers and relatives and 8.3% (1) by current or former stable partner and children. In conflicts with the police, 45.5% (10) had trouble with the police relating to prostitution, being 80% (8) due to complaints from residents about the workplace or police raid, 10% (1) related to loss of child custody because of her profession and 10% (1) due to prostitution when under age. 22.7% (5) were arrested; out of those, 60% (3) were held up to six hours, 20% (1) was held for 2,5 years and 20% (1) spent two months in prison and one year in the FEBEM. It was concluded that the rights insured by the Constitution are not being preserved in its entirety in the sampled group of CSW.
Keywords: Rights; Commercial sex workers; Violence